The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1590/s0102-09352008000500028
|View full text |Cite
|
Sign up to set email alerts
|

Perfil de natimortalidade de acordo com ordem de nascimento, peso e sexo de leitões

Abstract: Foram acompanhados 575 partos para avaliar a influência da ordem de nascimento, do sexo e do peso dos leitões na ocorrência de natimortos. Dos 7061 leitões, 90,2%, 6,0% e 3,8% nasceram vivos, natimortos ou mumificados, respectivamente. O percentual de partos com natimortos foi 44,5%. Partos com dois ou mais natimortos foram responsáveis por 63,1% das perdas por natimortalidade, embora tenham sido responsáveis por 17,2% das leitegadas. O percentual de natimortos aumentou com a ordem de nascimento; a maior taxa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
(15 reference statements)
0
4
0
1
Order By: Relevance
“…Thus, the prevalence of UTI is high, and its occurrence can vary according to different risk factors on farms. Borges et al (2008) reported that the number of stillbirths significantly increases with labor duration in pigs. In the present study, 33.3% of sows in group II and 43.3% in group I had labor longer than 360 min.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the prevalence of UTI is high, and its occurrence can vary according to different risk factors on farms. Borges et al (2008) reported that the number of stillbirths significantly increases with labor duration in pigs. In the present study, 33.3% of sows in group II and 43.3% in group I had labor longer than 360 min.…”
Section: Discussionmentioning
confidence: 99%
“…In a study using sows in 1 st to 10 th parity sequence. Borges et al (17) found that parity affects the mean neonatal piglet weight, and the best findings were shown in sows, in the 3 rd parity. However, the authors did not find a difference in relation to the number of born-alive piglets, dead neonatal piglets, or mummified embryos.…”
Section: Resultsmentioning
confidence: 98%
“…The use of vitamin 1,25-(OH) 2 D 3 and capsaicin in combination, either with a half dose or higher doses, was effective regarding the reproductive performance in both experiments. The positive results of vitamin 1,25-(OH) 2 D 3 , administered alone or in combination with capsaicin, regardless of the dose, on the frequency of dystocic births are promising, considering that modern sows are, due to hyper-prolificity [18], more likely to experience birth dystocia [5].…”
Section: Discussionmentioning
confidence: 99%
“…In this scenario, Blim et al [5] observed that a large proportion of sows have previously unknown deficiencies in electrolyte homeostasis (Ca, Mg, and P) around and during parturition, which is reflected by the large number of dystocic farrowings and the deficiencies in electrolyte concentrations during dystocia. Borges et al [18] suggested that the longer the calving time, the greater the number of stillborn, and the main reason for this is the interruption of blood flow in the placenta, resulting in hypoxia in the later animals, which, even if they do not die, may become lethargic and nonviable.…”
Section: Discussionmentioning
confidence: 99%